Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.3748/wjg.14.6299
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ghrelin on interdigestive contractions of the rat gastrointestinal tract

Abstract: In the interdigestive state, the stomach and small intestine show a remarkable motor pattern, known as the migrating motor complex (MMC) [1] . MMC consists of three phases; phaseⅠ(period of motor quiescence), phase Ⅱ (period of irregular low amplitude contractions) and phase Ⅲ (period of regular high amplitude contractions). In humans and dogs, MMC is usually observed every 90-120 min in the interdigestive state. In contrast, in rats, MMC cycle is less than 20 min and not so regular, compared to humans and dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
(45 reference statements)
0
24
0
Order By: Relevance
“…It remains to be determined whether lower blood glucose resulting from mild exercise has a similar effect. Ghrelin has been demonstrated to regulate interdigestive contractions in rats (Taniguchi et al 2008). Such effect of ghrelin can be blocked by vagotomy in vivo.…”
mentioning
confidence: 99%
“…It remains to be determined whether lower blood glucose resulting from mild exercise has a similar effect. Ghrelin has been demonstrated to regulate interdigestive contractions in rats (Taniguchi et al 2008). Such effect of ghrelin can be blocked by vagotomy in vivo.…”
mentioning
confidence: 99%
“…When the vagal nerve was cut, these effects were abolished (18). Peripheral administration of ghrelin also enhanced motility of the gastrointestinal tract (14,15,17,37 ]-GHRP-6 blocked the effect of ghrelin. These results suggest that ghrelin affects small intestinal motility by activating ghrelin receptors (GHS-R1a).…”
Section: Discussionmentioning
confidence: 99%
“…This may be the main factor leading to delayed small intestinal transit. Ghrelin can promote gastrointestinal tract motility if administered through central or peripheral channels (13,(15)(16)(17). Ghrelin exerts its role by activating ghrelin receptors (GHS-R1a) in central or peripheral tissues (2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the ghrelin receptor is expressed in the gastrointestinal tract, the effect of ghrelin on gastric motility has also been examined. In rats, ghrelin exerts stimulatory effects on motility of the antrum and duodenum in both fed and fasted states (Fujimiya, et al 2008), and Taniguchi et al reported that ghrelin infusion significantly increased motility index of phase III-like contractions at the antrum and jejunum in a dose dependent manner (Taniguchi, et al 2008). As well as the rat stomach, phase III-like contractions in mice were observed in the interdigestive state, and no spontaneous phase III-like contractions were found in vagotomized mice, suggesting that ghrelin-induced gastric phase III-like contractions are mediated via vagal cholinergic pathways in mice (Zheng, et al 2009).…”
Section: Roles Of Motilin and Ghrelin In Gastric Motilitymentioning
confidence: 99%